? PERSONAL COMPUTER BASED RAILWAY MONITORING AND SIGNALING SYSTEM (Biological Sciences - PJSIR, 1995)
To make railways a safer and more reliable mode of transport. it is quite necessary to introduce modernisation intoexisting railway signaling and control systems, because railway accidents cause great concern throughout the country.Major and minor railway accidents result from a seemingly intractable combination of human error, faulty signals. negligenceand so on. When the frequency of such occurrence reaches alarming proportions. there comes a great need toimprove signaling and communication systems. This clearly needs some rethinking. We propose and describe an implementationof a personalcomputercontrolled railwaymonitoringand signaling systemto avoid suchtypes of disasters.